25 years of the Group for Learning in Art and Design: A context. Issue 2 (1st November 2015) - Journeaux, Jill
In order to inform planning for and discussions at the 2015 Group for Learning in Art and Design (GLAD) Conference, which celebrated the 25th anniversary of the group, I compiled a brief chronological account of key events in that period. This is an edited version of the original, which is offered as an aide-memoire about the recent history of the UK Art and Design higher education (HE). I recognize that educational policy is not uniform across Northern Ireland, England, Scotland and Wales, for example, in relation to student tuition fees, which are not charged in Scotland. However, for the purposes of clarity this article uses the term 'UK' to point to general policy positions that relate to some or all of the United Kingdom.